2021
DOI: 10.1038/s41598-021-01585-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of feline leukemia virus infective stages by a novel nested recombinase polymerase amplification (RPA) and reverse transcriptase-RPA

Abstract: Feline leukemia virus (FeLV) is a major viral disease in cats, causing leukemia and lymphoma. The molecular detection of FeLV RNA and the DNA provirus are important for staging of the disease. However, the rapid immunochromatographic assay commonly used for antigen detection can only detect viremia at the progressive stage. In this study, nested recombinase polymerase amplification (nRPA) was developed for exogenous FeLV DNA provirus detection, and reverse transcriptase polymerase amplification (RT-RPA) was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
10
0
4
Order By: Relevance
“…They reported nested recombinase polymerase amplification (nRPA) and RT-RPA for the detection of FeLV DNA provirus and FeLV RNA, respectively. 14 Recently, Ghosh et al also reported two recombinase-based assays; RT-RPA and reverse transcription recombinase-aided amplification (RT-RAA) in the detection of SARS-CoV-2. Their findings revealed an equally promising diagnostic accuracy of the two methods, with a sensitivity of 76.32% (95% CI: 65.18-85.32%) by using RdRP and ORF1ab genes for RT-RPA and RT-RAA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They reported nested recombinase polymerase amplification (nRPA) and RT-RPA for the detection of FeLV DNA provirus and FeLV RNA, respectively. 14 Recently, Ghosh et al also reported two recombinase-based assays; RT-RPA and reverse transcription recombinase-aided amplification (RT-RAA) in the detection of SARS-CoV-2. Their findings revealed an equally promising diagnostic accuracy of the two methods, with a sensitivity of 76.32% (95% CI: 65.18-85.32%) by using RdRP and ORF1ab genes for RT-RPA and RT-RAA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 64% of the cats diagnosed with mediastinal lymphoma were FeLV positive by using a commercial test kit (immunochromatography assay), which detects the p27 antigen of the virus. The most recent study using nested recombinase polymerase amplification (nRPA) to detect exogenous FeLV DNA provirus and RT-PCR to detect FeLV RNA, showed that the FeLV detection rate in the regression phase was increased up to 45.8% compared to the rapid immunochromatographic assay ( 26 ). The number of FeLV-positive lymphomatous effusion in our study might have been higher if the molecular detection of the virus was used.…”
Section: Discussionmentioning
confidence: 99%
“…Podczas transmisji poziomej, zakażenie przenosi się przez bezpośredni kontakt, zwykle przez styczność ze śliną, np. przez jedzenie i picie ze wspólnej miski lub pokąsanie przez chorego osobnika (16). Zwierzęta mogą również zakazić się poprzez kontakt z wydzielinami i wydalinami, takimi jak: kał, mleko, mocz, płyny ustrojowe.…”
Section: Epidemiologia I Drogi Transmisjiunclassified
“…Zwierzęta mogą również zakazić się poprzez kontakt z wydzielinami i wydalinami, takimi jak: kał, mleko, mocz, płyny ustrojowe. Możliwa jest także transmisja wirusa w sposób jatrogenny podczas transfuzji krwi (16,17,20). FeLV jest przenoszony również przez ektopasożyty, takie jak pchły (30).…”
Section: Epidemiologia I Drogi Transmisjiunclassified
See 1 more Smart Citation